2017
DOI: 10.1007/s10597-016-0079-2
|View full text |Cite
|
Sign up to set email alerts
|

Service Users’ Perceptions of an Outreach Wellbeing Service: A Social Enterprise for Promoting Mental Health

Abstract: Inadequate provision and limited access to mental healthcare has been highlighted with the need to offer more contemporary ways to provide clinically effective interventions. This study aimed to present an insight into service users’ perceptions of an outreach Wellbeing Service (WBS), providing psychological therapy in social settings. Descriptive and thematic analysis was undertaken of 50 returned surveys. Comparison of initial and final mental health measures demonstrated a significant improvement in all out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Immigrant service providers argued for community‐based mental health initiatives that integrate with other social services accessed by immigrants and refugees. The use of case managers and community navigators who serve as community liaisons continues to show promising results (Hartley ; Hochhausen et al . ; Shommu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Immigrant service providers argued for community‐based mental health initiatives that integrate with other social services accessed by immigrants and refugees. The use of case managers and community navigators who serve as community liaisons continues to show promising results (Hartley ; Hochhausen et al . ; Shommu et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature we reviewed, patient wellbeing was examined in terms of clinical outcomes and the reported impact of the interventions on patients. Using standardised measures, significant improvement was seen in depression 22 , 26 following increased access to healthcare. However, there were mixed results in terms of anxiety in the same studies.…”
Section: Resultsmentioning
confidence: 99%
“…Five articles examined the use of digital communications via email, 21 text message, 22 patient portal 23 or (two studies of the same) virtual clinic. 24 , 25 The other studies focussed on increasing patient access to healthcare via an outreach service, 26 drive to increase uptake of Improving Access to Psychological Therapies (IAPT), 27 increased contact with primary care clinicians, 28 , 29 through increased contact with a nurse as part of a diabetes education programme 30 and through a supported housing programme. 31 …”
Section: Methodsmentioning
confidence: 99%
“…[53] 'Community-based protection and mental health and psychosocial support (MHPSS)' is an excellent resource developed by UNHCR to use as a guide for service providers. [54] Studies have reported the success achieved by case managers and community navigators in the roles of community liaisons. [55,56] Outreach programs for refugees who cannot otherwise reach out to mainstream mental healthcare services due to system complicacy and navigation issues have been recommended in this study, as well in other studies.…”
Section: Rghmentioning
confidence: 99%